The impact of violence on healthcare workers' mental health in conflict based settings amidst COVID‐19 pandemic, and potential interventions: A narrative review. Issue 6 (6th November 2022) - Rija, Aiman; Islam, Zarmina; Bilal, Wajeeha; Qamar, Khulud; Gangat, Shazil Ahmed; Abbas, Samina; Mirha, Hania Tul; Mohanan, Parvathy; Rahmat, Zainab Syyeda; Shaeen, Sean Kaisser; Djedid, Selma Nihel Klouche; Essar, Mohammad Yasir; et al.
Abstract: Healthcare workers (HCWs) have faced an increased amount of mental health struggles amidst the COVID‐19 pandemic. However, those in conflict‐based settings with fragile healthcare systems meet additional challenges. This study reviews violence, conflict and mental health among HCWs in five countries: Syria, Palestine, Yemen, Afghanistan and Lebanon. Our study reports that HCWs are targeted by violence, bombings, mistreatment and different forms of abuse, including verbal and physical. With the additional burdens of the pandemic including prolonged working hours, limited resources and insufficient humanitarian aid, the healthcare workers fall victim to increased levels of burnout and mental illnesses. The situation leads to dire consequences on their personal lives and professional development, compelling them to quit their job or country all together. Although healthcare workers remain resilient in these conflict‐based settings, immediate interventions are required to prevent violence against them and cater to their rapidly declining mental health.